Quality of training in oral health educational programs: What do primary healthcare providers think? - Peimaneh Hosseini Dastnaei; Zahra Saied Moallemi; Arash Najimi (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Due to changes in scientific findings and assigned tasks, continuing education and other enabling programs are increasingly critical for primary healthcare providers to keep them up-to-date in delivering oral health services. Planning these educational courses based on actual PHCPs' needs is fundamental to provide effective ones. The purpose of this study was to elucidate the experiences and needs of PHCPs regarding the quality of the oral health training provided in continuing education and other enabling courses. SUBJECTS AND METHODS: A qualitative study with content analysis approach was conducted in Najaf-Abad, Isfahan, Iran, in 2017. Data were gathered through in-depth semi-structured interviews with 19 primary healthcare providers. The sampling was started with purposeful method and continued through snowball method. Qualitative data were coded and analyzed using MAXQDA (VER 12). RESULTS: Factors affecting the quality of oral health training were categorized into three themes and nine subthemes, including instructor's related factors (knowledge, skills, and relevant experiences), educational content (content relevance, content innovation, and content update), and teaching methods and educational tools (fitting educational contents, covering learners' needs, and considering available possibilities). CONCLUSION: Instructors with inadequate level of knowledge, skills, and relevant experiences as well as inappropriate selection of educational content, teaching methods, and educational tools, were recognized as affecting factors on the quality of oral health training and effectiveness of continuous education and enabling programs.